Involving trained community health mediators in COVID-19 prevention measures. A process evaluation from Bremen, Germany - Brand, Tilman; Gerstmann, Marieke; Samkange-Zeeb, Florence; Zeeb, Hajo (Frontiers in Digital Health, 2023)
The objective was to assess the feasibility of incorporating trained community health mediators in COVID-19 prevention in a multicultural and disadvantaged setting in Bremen, Germany. Specifically, we aimed to develop and implement measures corresponding to the needs of the residents and to analyse the role of digital communication tools and sustainability factors of the health mediator approach.A comprehensive process evaluation using 41 qualitative interviews with residents, mediator short surveys and group discussions, work documentation sheets, and a stakeholder workshop was carried out.Uncertainties due to changing regulations, a lack of trust and fear of potential side effects were major themes identified in the needs assessment. The eight mediators documented more than 1600 contacts. Digital communication via Facebook was a useful tool, but personal contacts remained crucial for communicating with residents. The participatory approach, multilingualism and the flexibility to react to dynamic situations were identified as relevant factors for the success and sustainability of the health mediator approach.Multilingual health mediators can facilitate contact with and dissemination of health information to different communities and also can play an important role in pandemic preparedness.